Modern mathematical statistics with applications [ - Devore; Berk (Belmont, CA: Thomson Brooks/Cole, 2007)
CD-ROM contains datasets formatted for MINITAB, SAS, SPSS, JMP, Microsoft Excel, and ASCII, as well as MINITAB macros for doing bootstrapping and permutation tests. System requirements (PC) for accompanying CD-ROM: Windows 98, ME, 2000, XP (not NT); Pentium II, 233 MHz or higher; 32MB RAM (64MB recommended); 800 x 600, 16-bit high-color display; 16-bit sound card; speakers or headphones; 8xCD-ROM. System requirements (MAC) for accompanying CD-ROM: Mac OS 8.6 or later; PowerPC processor or later; 64MB RAM; 800 x 600, 16-bit high-color display; 16-bit sound card; speakers or headphones; 8xCD-ROM
To accompany textbook titled "Modern mathematical statistics with applications / Jay L. Devore, Kenneth N. Berk"
AUP
Keywords: Mathematical statistics; Mathematical statistics -- -- Problems, exercises, etc